Highly Efficient Large-Area Organic Photovoltaic Module with a 350 nm Thick Active Layer Using a Random Terpolymer Donor - Park, So Hyun; Park, Sungmin; Kurniawan, Daniel; Son, Jeong Gon; Noh, Jun Hong; Ahn, Hyungju; Son, Hae Jung (AMER CHEMICAL SOC, 2020)
Random terpolymers are developed by incorporating small portions of benzodithiophene into a highly crystalline copolymer of terthiophene and difluorobenzo-thiadiazole, BDT-Th0. The bulk-heterojunction (BHJ) of the copolymer BDT-Th0 is formed by a process of rapid solid-liquid phase demixing of polymer crystallites, which results in an irregular and an unclear phase separation with a large polymer aggregation. By contrast, the random terpolymer BDT-Th10, which was prepared using a 10% feed molar ratio of a benzodithiophene moiety, shows a slower and a gradual formation of the polymer packing structures without substantial agglomeration from loosely packed pseudocrystallites in precursor solution. This results in an optimal BHJ morphology with an appropriate phase separation and improved domain purity. BDT-Th10 achieves a high solar cell efficiency of 7.74% by successfully reproducing the optimized BHJ morphology of small cells into 58.5 cm(2)-sized modules with 350 nm film thickness, whereas the copolymer shows an irreproducible property with a much decreased efficiency of 4.37%. This result is among the highest efficiencies of high-performance large-area PSC modules with such a thick active film.
Keywords: POLYMER SOLAR-CELLS; CHARGE-TRANSPORT; PERFORMANCE; AGGREGATION; GENERATION; NETWORK; YIELD; FILM